Sudden Cognitive Decline in Bipolar Mood Disorder Patient with Underlying Severe Tardive Dyskinesia After the Failure of His Deep Brain Stimulation Device Battery - Nathratul Ayeshah Zulkifli; Jesjeet Singh Gill; Ng Chong Guan (USIM Press, 2024)
Vol. 7 No. 3 (2021): Special Issue on Clinical Scenarios In Medicine, A Malaysian Experience (Case Report)